Highly-enhanced propagation of long-range kinks in heterogeneous media - Jorge A. González; Alberto Bellorín; Luis E. Guerrero; Salvador Jiménez; Juan F. Marín (Journal of High Energy Physics)
Abstract We investigate a field-theoretical model that describes the interaction between kinks and antikinks and between kinks and other heterogeneous fields and impurities. We show that the long-range kink can tunnel through a barrier created by heterogeneous fields and impurities even when the energy of the center of mass of the kink is less than the height of the energy barrier. We also study the conditions under which the kink can pass freely through a disordered medium. We introduce the concept of “effective translational symmetry”. We compare our results with those from recent papers published in this journal, where the Bogomol’nyi-Prasad-Sommerfield property is discussed.